OBTAINING SYNTHETIC GASOLINE FROM NATURAL GAS (Neo Science Peer Reviewed Journal, 2024)
High prices for oil and energy, which have persisted for a long time, as well as the increasing demand for automobile fuel, force us to look for alternative sources of production of fuels and chemical products. For this purpose, the article considered the possibility of producing synthetic gasoline from natural gas. The process of producing gasoline from synthesis gas using the Fischer-Tropsch method has been studied. Gasoline was obtained in laboratory conditions from natural gas on an iron catalyst under medium pressure. The obtained synthesis products were compared with the products obtained by the Fischer-Tropsch method.